2006
DOI: 10.1080/10494820600852795
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal perspective regarding the use of VLEs by higher education institutions in the United Kingdom

Abstract: conducted surveys into issues relating to the acquisition, use, management and support of Virtual Learning Environments (VLEs). A number of other studies provide information on these issues during this period. Together they provide a substantial body of evidence that allows an analysis of the factors that enhance or inhibit institutional take-up and support provision for VLEs within the UK higher education sector.There is clear evidence of increasing use of VLEs but not of widespread change in pedagogic practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
86
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 1 publication
7
86
0
2
Order By: Relevance
“…Baker and Yacef [10] suggest that EDM is used to improve student model, improve domain model and analyze the support of learning system. They categorized the EDM methods into prediction, clustering, association rule mining, a discovery with models and distillation of data for human judgment.…”
Section: Educational Data Mining Methods and Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Baker and Yacef [10] suggest that EDM is used to improve student model, improve domain model and analyze the support of learning system. They categorized the EDM methods into prediction, clustering, association rule mining, a discovery with models and distillation of data for human judgment.…”
Section: Educational Data Mining Methods and Applicationsmentioning
confidence: 99%
“…This means that data from different levels such as the school level, the teacher level, the classroom level, the student level, the session level, the answer level and the keystroke level are nested inside one another [10], [11]. Also, there are three important data attributes need to be considered while capturing educational data which are: time, sequence and context.…”
Section: E-learning and Educational Data Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, universities have adopted a Virtual Learning Environment (VLE) in order to provide flexibility in the teaching and learning service that they offer to their students allowing them to have access to numerous online learning material and tools (Browne et al 2006). However, the way that VLE has been adopted is mainly to support the traditional way of teaching (Doreen and Yazrina 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Browne et al (2006) found that something like 95 per cent of higher education (HE) institutions in the UK now have a VLE. Bell et al (2002) note that VLE usage is not uniform however.…”
mentioning
confidence: 99%